The effect of cervical cerclage on pregnancy outcomes in women following conization. (October 2014) - Rafaeli-Yehudai, Tal; Kessous, Roy; Aricha-Tamir, Barak; Sheiner, Eyal; Erez, Offer; Meirovitz, Michai; Mazor, Moshe; Weintraub, Adi Y.
Abstract Objectives: To determine the effect of cervical cerclage on obstetrical complications and perinatal outcomes of patients following conization. Design: A retrospective population based cohort study. Setting: Tertiary academic medical center that covers all the deliveries of the region. Population: All patients with previous cervical conization who delivered between the years 1994–2011. Methods: A retrospective population based study. Main outcome measures: The effect of cerclage placement on the rate of preterm birth. Results: During the study period there were 109 deliveries of patients following a cervical conization. Cervical cerclage was placed in 22 deliveries that served as the study group and the rest (n = 87) served as the comparison group. The rate of early preterm delivery (PTD; <34 weeks) was significantly higher in women who had a cerclage. In a logistic regression model, cerclage was found to be an independent risk factor for early PTD. Conclusion: Cerclage is an independent risk factor for early PTD In patients who had a conization due to CIN.